Upaya Meningkatkan Keamanan Lingkungan Pelestarian dan Pengembangan Ekowisata Hutan Mangrove Wonorejo: melalui Kerja Sama Green Sister City Surabaya – Kitakyushu - Candelaria, Arizki Putri (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2024)
The city of Surabaya faces various environmental issues, including air pollution, water contamination, and waste management. Addressing these problems requires a holistic approach through the utilization of vegetative areas, such as mangrove forests, which have many essential functions for the environment and human life. In an effort to conserve the mangrove forests in Surabaya, the city has established a partnership with Kitakyushu, Japan, which has successfully overcome similar environmental crises in the past. This research aims to examine how the experiences and successes of Kitakyushu can be applied in Surabaya to develop mangrove forest ecotourism, with the goal of improving environmental quality and community well-being. The methodology used is qualitative-descriptive, with data collected through interviews and document analysis. The research findings indicate that Kitakyushu's successful experience in addressing environmental issues serves as an inspiration for Surabaya. This collaboration includes various mangrove forest conservation programs and ecotourism development, which have successfully enhanced environmental quality and public awareness. In conclusion, international cooperation through paradiplomacy, such as this sister city relationship, can be an effective model for addressing environmental issues and improving local community welfare. Kota Surabaya menghadapi berbagai permasalahan lingkungan, termasuk polusi udara, pencemaran air, dan pengelolaan sampah. Penanganan masalah ini membutuhkan pendekatan holistik melalui pemanfaatan kawasan vegetasi, seperti hutan mangrove, yang memiliki banyak fungsi penting bagi lingkungan dan kehidupan manusia. Dalam upaya melestarikan hutan mangrove di Surabaya, kota ini menjalin Kerjasama sister city dengan Kitakyushu, Jepang, yang telah berhasil mengatasi krisis lingkungan serupa di masa lalu. Penelitian ini bertujuan mengkaji bagaimana pengalaman dan keberhasilan Kitakyushu dapat diterapkan di Surabaya untuk mengembangkan ekowisata hutan mangrove, guna meningkatkan kualitas lingkungan dan kesejahteraan masyarakat. Metode yang digunakan adalah kualitatif-deskriptif, dengan pengumpulan data melalui wawancara dan penelusuran dokumentasi. Hasil penelitian menunjukkan bahwa pengalaman sukses Kitakyushu dalam mengatasi permasalahan lingkungan menjadi inspirasi bagi Surabaya. Kerjasama ini mencakup berbagai program pelestarian hutan mangrove dan pengembangan ekowisata, yang berhasil meningkatkan kualitas lingkungan dan kesadaran masyarakat. Kesimpulannya, kerjasama internasional melalui paradiplomasi, seperti hubungan sister city ini, dapat menjadi model efektif dalam mengatasi isu-isu lingkungan dan meningkatkan kesejahteraan masyarakat lokal.